A Combination of X‐Ray Tomography and Carbon Binder Modeling: Reconstructing the Three Phases of LiCoO2 Li‐Ion Battery Cathodes. Issue 8 (27th January 2014) - Zielke, Lukas; Hutzenlaub, Tobias; Wheeler, Dean R.; Manke, Ingo; Arlt, Tobias; Paust, Nils; Zengerle, Roland; Thiele, Simon
<x xml:space="preserve">Abstract</x> X‐ray tomography allows the active‐material domain (LiCoO2) of Li‐ion battery cathodes to be imaged, but it is unable to resolve the carbon‐binder domain (CBD). Here, a new method for creating a complete 3D representation (virtual design) of all three phases of a cathode is provided; this includes the active‐material domain, the CBD, and the electrolyte‐filled pore space. It combines X‐ray tomographic data of active material with a statistically modeled CBD. Two different statistical CBD morphology models are compared as examples: i) a random cluster model representing a standard mixture of carbon black and polyvenylidene fluoride (PVDF) and ii) a fiber model. The transport parameters are compared in a charged and a discharged cathode. The results demonstrate that the CBD content and morphology changes the ionic and electronic transport parameters dramatically and thus cannot be neglected. Calculations yield that the fiber model shows up to three times higher electrical conductivity at the same CBD content (discharged case) and better ionic diffusion conditions for all CBD contents. In the charged case, the morphology impact on electrical conduction is small. This effective method to generate transport parameters for different CBDs can be transferred to other CBD morphologies and electrodes.